Towards understanding always on marketing practices - Malin, Heidi (My University, 2019)
Digitalization, social media and a world, that is moving in a faster pace all the time, have made it necessary for the brands to change their way of marketing and communicating. Consumers expect brands to be present all the time and produce continuous and timely content. Always on marketing is a rising way of marketing communications, which is usually seen as continuous and reactive, with no specific start or end dates. The purpose of this research is to investigate always on marketing practices. This goal was broken down into three different research questions: What is always on marketing and how is it conducted, how different content strategies can be applied to always on marketing, and what advantages or disadvantages always on marketing might have. The research was conducted with qualitative theme interviews. Five different interviews were organized. Interviewees were experts on always on marketing from Finnish advertising agencies, that have been offering always on marketing for their customers for multiple years. Questions were based on the theoretical background, which was built based on marketing on social media. Analysis was done based on the theoretical background. A significant finding as well as a benefit for brands that conduct always on marketing were the opportunities created by this type of marketing. When brands continuously react to current events and topics, they are at the same time responding to the continuous opportunities provided by the world. They have the opportunity of keeping communication channels open with the consumers. When these communication channels are open, the brand has the opportunity to engage in a two-way communication with the consumers and make it able to respond faster and better prepared to potential crisis situations. When continuous content is provided frequently, brand also has an increased chance for its content to go viral, because it has more opportunities for it. This means that the opportunity for earned visibility is much higher, benefitting the brand. This increases the awareness among the general public, possibly leading to brand preference in a long run.

Digitalisaatio, sosiaalinen media ja koko ajan hektisempi maailma ovat vaatineet brändejä muuttamaan markkinointitapojaan ja kommunikointiaan. Kuluttajat odottavat brändien olevan läsnä koko ajan ja tuottavan jatkuvaa ja ajankohtaista sisältöä. Always on -markkinointi on uudenlainen tapa markkinoida –sitä pidetään yleensä jatkuvana ja reaktiivisena ilman aloitus- tai lopetuspäiviä. Tämän tutkimuksen tarkoituksena oli lisätä ymmärrystä always on -markkinoinnista ja sen keskeisistä käytännöistä.. Tämä tavoite jaettiin kolmeen erilaiseen tutkimuskysymykseen: Mitä always on -markkinointi on ja miten sitä toteutetaan, kuinka erilaisia sisältöstrategioita voidaan soveltaa always on -markkinointiin, ja miten se voi olla hyödyksi brändille. Empiirinen tutkimusaineisto kerättiin teemahaastatteluin. Viittä kokenutta always on -markkinointiviestinnän asiantuntijaa suomalaisista mainostoimistoista haastateltiin. Haastattelukysymykset pohjautuivat yleiseen teoreettiseen viitekehykseen, joka oli rakennettu lähinnä sosiaalisen median kautta tapahtuvan markkinoinnin kirjallisuutta hyödyntäen. Teoriataustaan nojauduttiin haastatteluaineistoa tulkittaessa. Alwayn on -markkinointi luo selkeitä mahdollisuuksia brändeille. Kun brändit reagoivat jatkuvasti ajankohtaisiin tapahtumiin ja aiheisiin, ne vastaavat samalla median tarjoamiin jatkuviin mahdollisuuksiin. Brändeillä on mahdollisuus pitää viestintäkanavat avoimina kuluttajien kanssa. Kun nämä viestintäkanavat ovat auki, brändeillä on mahdollisuus käydä kaksisuuntaista viestintää kuluttajien kanssa, jolloin ne kykenevät reagoimaan nopeammin ja paremmin varautuneena mahdollisiin kriisitilanteisiin. Kun jatkuvaa sisältöä tarjotaan usein, brändillä on myös lisääntynyt mahdollisuus viraalille sisällölle, koska sillä on enemmän mahdollisuuksia siihen. Tämä tarkoittaa, että mahdollisuus ansaittuun näkyvyyteen on paljon suurempi. Tämän myötä tunnettuus kasvaa, mikä johtaa mahdollisesti brändin suosimiseen pitkällä tähtäimellä.
Keywords: social media marketing, content marketing, always on marketing